PENGEMBANGAN OBJEK WISATA BUKIT DAMI DENGAN KONSEP EKOWISATA DI DESA TIGASAN WETAN, LECES, PROBOLINGGO - Mutinda Teguh Widayanto (TAAWUN, 2021)
Improving people's welfare is the national aim that is tried to be realized with various efforts. Optimizing the potential of natural resources as a tourism object is one of the way to make this dream come true. In Tigasan Wetan Village, Leces District, Probolinggo Regency, there is an hill named “Bukit Dami” which has the potential to be developed as an ecotourism object. The Youth Group “Teras Tanah” saw this potential and tried to develop it as a tourist attraction even though it was not optimal. The KKN Team of Panca Marga University was moved to carry out community service activities with the aim to optimizing the existence of Bukit Dami as an object of ecotourism. In collaboration with the Teras Tanah Youth Group, several activities have been carried out so that it is hoped that this Ecotourism object can develop and provide benefits to the surrounding community.